Impact of COVID‐19 in hematopoietic stem cell transplant recipients: A systematic review and meta‐analysis. Issue 2 (25th January 2022) - Shahzad, Moazzam; Chaudhary, Sibgha Gull; Zafar, Muhammad U.; Hassan, Maha A.; Hussain, Ali; Ali, Fatima; Anwar, Iqra; Ahmed, Mamoon; Ahmed, Nausheen; Khurana, Sharad; Rauf, Muhammad A.; Anwar, Faiz; et al.
Abstract: Background: Hematopoietic stem cell transplant (HSCT) recipients are at increased risk of mortality and morbidity with coronavirus disease 2019 (COVID‐19) due to severe immune dysfunction. Methods: A literature search was performed on PubMed, Cochrane, and Clinical trials.gov from the date of inception to 12/08/2021. We identified 19 original studies reporting data on COVID‐19 in HSCT recipients after screening 292 articles. Data were extracted following preferred reporting items for systematic reviews and meta‐analysis guidelines. Quality evaluation was done using the National Institutes of Health (NIH) quality assessment tool. Inter‐study variance was calculated using Der Simonian–Laird Estimator. Pooled analysis was conducted using MetaXL. A random‐effects model was used to estimate the proportions with 95% confidence intervals (CI). Results: Of 6711 patients in 19 studies, 2031 HSCT patients with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection were analyzed. The median age of patients was 56.9 (range 1–81.6) years, and 63% patients were men according to 14 studies. The median time from transplant to SARS‐CoV‐2 infection for autologous (auto) and allogeneic (allo) HSCT patients was 23.2 (0.33–350.5) months and 16.4 (0.2–292.7) months, respectively. The median follow‐up time after COVID‐19 diagnosis was 28 (0–262) days. The COVID‐19 mortality rate was 19% (95% CI 0.15–0.24, I 2 = 76%, n = 373/2031). The pooled mortality rate was 17% (95% CI 0.12–0.24, I 2 = 78%, n = 147/904) in auto‐HSCT patients and 21% (95% CI 0.16–0.25, I 2 = 60%, n = 231/1103) in allo‐HSCT patients. Conclusions: HSCT recipients have a high risk of mortality and clinical complications due to COVID‐19. There is a need for ongoing vigilance, masks, and social distancing, vaccination, and aggressive management of SARS‐CoV‐2 infection in HSCT recipients.